Laparoscopic versus laparotomy: Staging surgery for endometrial cancer - Malaysia's early experience - Wan Ahmad Hazim Wan Ghazali; Siti Amira Jamil; Ili Abdullah Sharin (Wolters Kluwer Medknow Publications, 2019)
Objective: The objective of the study is to assess the efficacy of laparoscopy compared with laparotomy in extrafascial hysterectomy and lymphadenectomy for endometrial cancer. Design: This was a retrospective study of small cases over a 5-year period. Setting: This study was conducted in Putrajaya Hospital, a district hospital with consultant care level in obstetrics and gynecology. Sample: Forty women presented with confirmed cases of endometrial cancer based on histopathology result and underwent extrafascial hysterectomy with or without lymphadenectomy between January 2010 and December 2014. Materials and Methods: Patient outcomes were compared between 26 women who underwent laparoscopic total hysterectomy with or without lymphadenectomy and 14 women who underwent open laparotomy extrafascial hysterectomy with or without lymphadenectomy. Data were collected using electronic medical records. Main Outcome Measures: Postoperative outcomes, operative time, total intraoperative blood loss, number of lymph nodes harvested, and total days of postoperative stay were obtained. Results: There was a significant reduction in operative blood loss in the laparoscopic group with mean 262.50 ± 47.87 and laparotomy group with mean 381.82 ± 138.33, 95% confidence interval, P < 0.05. Postoperative hospital stay was also significantly reduced in the laparoscopic group, where the mean postoperative stay in laparoscopic group was 2.5 ± 2.0 days and laparotomy 5.0 ± 3.6 days. There was no significant difference in mean operative time (the mean operative time: 256 ± 76.40 for laparotomy and 288.75 ± 43.66 for the laparoscopic approach). More number of lymph nodes were harvested laparoscopically (29.75 ± 16.59) than laparotomy (23.0 ± 12.62); however, this was not significant. Conclusions: Laparoscopic surgery had significant lesser blood loss and it is comparable to laparotomy in the surgical management of endometrial cancer. Experienced surgeon will be able to perform hysterectomy and lymphadenectomy as equally good to laparotomy with adequate tumor excision and complete staging.